Preparation method of pre-fibration polymer solid electrolyte and product and application of pre-fibration polymer solid electrolyte
By mixing prefibrotic polytetrafluoroethylene dry powder with sulfide lithium phosphorus thiochlorochloride electrolyte, a room temperature rolling process is used to prepare a sulfide solid electrolyte composite film, which solves the problem of sulfide electrolyte preparation and the problem of low energy density of all-solid lithium batteries, and achieves the preparation of electrolyte membranes with high mechanical strength and high ionic conductivity, which improves the actual energy density of the battery.
Patent Information
- Application Number
- CN202411893655.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
In the preparation process of the existing sulfide solid electrolyte, a thicker electrolyte layer needs to be formed under high pressure, and the positive electrode material needs to be fully mixed with a large amount of sulfide electrolyte to prepare a positive electrode in an integrated manner, which makes the preparation of sulfide solid electrolyte a difficult problem, and the actual specific energy of an all-solid lithium battery is far lower than the theoretical value.
The sulfide solid electrolyte composite film was directly prepared by mixing prefibrotic polytetrafluoroethylene (PTFE) dry powder and sulfide lithium phosphorus thiochloride (Li6PS5Cl) electrolyte.
This method avoids high-cost and high-energy consumption ball milling and hot pressing operations, reduces preparation energy consumption and equipment costs, significantly improves the mechanical strength of the electrolyte membrane, retains high ionic conductivity, and improves the actual specific energy of all solid-state lithium batteries.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials for solid-state lithium batteries, and to a method for preparing a pre-fiberized polymer solid electrolyte, and its products and applications, and in particular to a method for preparing a sulfide electrolyte composite membrane using a pre-fiberized polymer binder at room temperature, and its development and application in the field of solid-state batteries. Background Art
[0002] All-solid-state batteries have become a research hotspot in battery development. Compared with commercial liquid electrolytes, the use of solid electrolytes in solid-state batteries can effectively improve battery safety, power density, and energy density. Matching solid electrolytes with high-capacity positive and negative electrodes can have higher mechanical strength and can effectively inhibit the generation of lithium dendrites during the battery's charge and discharge process, giving the battery a longer cycle life. Therefore, the current society's research on all-solid-state batteries continues to heat up.
[0003] Among inorganic solid electrolytes, sulfide solid electrolytes (SSE) such as Li2S-P2S5, Li 10 GeP2S 12 and Li6PS5X (argentum sulfide, X = Cl, Br, I), etc., due to their high room temperature ionic conductivity (10 -3 ~10 -2 mS / cm) and has become a research hotspot. However, the sulfide electrolyte has low stiffness and a Young's modulus of about 20 GPa. Practical use requires the formation of a thicker (1000 μm) electrolyte layer under pressure (300 MPa). At the same time, in order to achieve full contact between the cathode active material powder and the solid electrolyte and reduce the electrode material / electrolyte interface impedance, the cathode material needs to be fully mixed with a large amount of sulfide electrolyte to prepare an integrated cathode composite electrode, which makes the preparation of sulfide solid electrolyte a difficult problem. It should be pointed out that due to the large-scale use of sulfide solid electrolytes in the electrolyte layer and the composite cathode, the actual specific energy of all-solid-state lithium batteries is much lower than the theoretical value, which also restricts its practical application.
[0004] In order to reduce the amount of electrolyte and improve the actual specific energy of solid-state batteries, the method of preparing sulfide electrolyte film by polymer bonding is generally used to improve the mechanical strength of the electrolyte layer. The preparation methods of sulfide electrolyte film mainly include slurry coating method and dry powder rolling method. The slurry coating method can use the existing lithium-ion battery process equipment, but there may be side reactions between the solvent and the electrolyte, and the ionic conductivity will drop significantly by an order of magnitude after the solid electrolyte is dissolved and precipitated. The dry powder rolling method does not require the use of solvents, avoiding side reactions between the solvent and the sulfide electrolyte and the reduction of ionic conductivity caused by this process. Dry preparation generally uses hot pressing, for example, hot pressing polytetrafluoroethylene (PTFE) or polyethylene oxide (PEO) and sulfide electrolyte into a composite electrolyte membrane, but the hot pressing operation not only requires a special hot rolling device, but also has high energy consumption. Summary of the invention
[0005] The present invention aims to provide a method for preparing a pre-fiberized sulfide solid electrolyte composite membrane.
[0006] Another object of the present invention is to provide a pre-fiberized sulfide solid electrolyte composite membrane product prepared by the above method.
[0007] Another object of the present invention is to provide an application of the above product.
[0008] The object of the present invention is achieved by the following scheme: a method for preparing a pre-fiberized sulfide solid electrolyte composite membrane, firstly preparing a pre-fiberized PTFE dry powder by demulsifying and drying a polytetrafluoroethylene (PTFE) emulsion, then mixing a sulfide lithium phosphorus sulfur chlorine (Li6PS5Cl) electrolyte and fiberized PTFE, and directly preparing a sulfide solid electrolyte composite membrane by a solvent-free dry process of rolling at room temperature, comprising the following steps: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a scraper of 300-600 μm, then place the glass plate in a vacuum oven, keep it at 120°C for 8 h to evaporate the solvent, put the glass plate in a glove box, scrape off the PTFE film under argon protection and crush it to obtain pre-fiberized PTFE dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Mix sulfide lithium phosphorus sulfur chlorine Li6PS5Cl electrolyte and pre-fiberized PTFE dry powder in a mixing ratio of 0.5~2.5 wt%, stir the mixture thoroughly in a mortar and transfer it to a smooth stainless steel plate, and repeatedly roll-form it with a stainless steel roller to form an electrolyte membrane with a thickness of 20~30μm, which is the sulfide Li6PS5Cl solid electrolyte film.
[0009] The mixing ratio of the pre-fiberized PTFE dry powder and the sulfide lithium phosphorus sulfur chlorine (Li6PS5Cl) electrolyte used in the present invention is controlled within the range of 0.5 to 2.5 wt%; The present invention also provides a pre-fiberized sulfide solid electrolyte composite membrane, which is prepared according to the above method.
[0010] The present invention also provides an application of a pre-fiberized sulfide solid electrolyte composite in an all-solid-state lithium battery.
[0011] When solid-state batteries are used, the pre-prepared pre-fiberized sulfide solid electrolyte composite membrane needs to be placed in a mold and surface pressed at a pressure of 300 MPa. When assembling the battery, carbon-coated LiCoO2 material is selected as the positive electrode and lithium-indium alloy as the negative electrode to prepare a suitable solid-state battery.
[0012] The method firstly prepared pre-fiberized PTFE dry powder by demulsifying and drying the polytetrafluoroethylene (PTFE) emulsion, then mixed the sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte and fiberized PTFE in appropriate proportions, and directly prepared the sulfide solid electrolyte composite membrane by a solvent-free dry process of roller pressing at room temperature. The pre-fiberized solid sulfide electrolyte film avoids high-cost and high-energy operations such as ball milling and hot pressing, and reduces the energy consumption and equipment cost of preparation. The material can be effectively used in the preparation of solid-state batteries, fully retaining the structure and performance of the electrolyte material. This method is a solid electrolyte film-forming technology with application prospects, which has important application value for the development of solid-state batteries.
[0013] The electrolyte film not only reduces the amount of electrolyte used, significantly improves the mechanical strength of the electrolyte film, but also retains the high ionic conductivity of the sulfide electrolyte (3.06*10-4 S / cm). This method can fully retain the structure and performance of the electrolyte material and is a solid electrolyte film-forming technology with application prospects; the electrolyte film can also be used in the preparation of composite positive electrodes to construct all-solid-state thin-film lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the ionic conductivity curve of the pre-fiberized sulfide solid electrolyte composite membrane. DETAILED DESCRIPTION
[0015] This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0016] Embodiment 1: A pre-fiberized sulfide solid electrolyte composite membrane is first prepared by demulsifying and drying a polytetrafluoroethylene (PTFE) emulsion to prepare a pre-fiberized PTFE dry powder, and then mixing a sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte and fiberized PTFE to directly prepare a sulfide solid electrolyte composite membrane through a solvent-free dry process of roller pressing at room temperature. The preparation is carried out according to the following steps: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a 300 μm scraper, then place the glass plate in a vacuum oven and keep it at 120°C for 8 h to evaporate the solvent; finally, put the glass plate in a glove box, scrape off the PTFE membrane under argon protection and crush it to obtain PTFE membrane dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Weigh 0.2 g of pre-fiberized PTFE dry powder and 20 g of sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte, mix them in a mass ratio of 1 wt% of PTFE dry powder and Li6PS5Cl electrolyte, stir the mixture thoroughly in a mortar and pestle, transfer the mixture to a smooth stainless steel plate, and repeatedly roll-form it with a stainless steel roller to form an electrolyte membrane with a thickness of 20 μm, which is the pre-fiberized sulfide Li6PS5Cl solid electrolyte composite membrane.
[0017] The prepared pre-fiberized sulfide solid electrolyte composite membrane was placed in a mold, surface pressed at a pressure of 300 MPa, and the ionic conductivity was tested.
[0018] Embodiment 2: A pre-fiberized sulfide solid electrolyte composite membrane is similar to Example 1 and is prepared according to the following steps: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a 400 μm scraper, then place the glass plate in a vacuum oven and keep it at 120°C for 8 h to evaporate the solvent; finally, put the glass plate in a glove box, scrape off the PTFE membrane under argon protection and crush it to obtain PTFE membrane dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Weigh 0.4 g of pre-fiberized PTFE dry powder and 20 g of sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte, mix them in a mass ratio of 2 wt% of PTFE dry powder and Li6PS5Cl electrolyte, stir the mixture thoroughly in a mortar and pestle, and transfer the mixture to a smooth stainless steel plate. Repeatedly roll-form the mixture with a stainless steel roller to form an electrolyte membrane with a thickness of 30 μm, which is the sulfide Li6PS5Cl solid electrolyte film.
[0019] Embodiment 3: A pre-fiberized sulfide solid electrolyte composite membrane is similar to Example 1 and is prepared according to the following steps: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a 600 μm scraper, then place the glass plate in a vacuum oven and keep it at 120°C for 8 h to evaporate the solvent; finally, put the glass plate in a glove box, scrape off the PTFE membrane under argon protection and crush it to obtain PTFE membrane dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Weigh 0.5 g of pre-fiberized PTFE dry powder and 20 g of sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte, mix them in a mass ratio of 2.5 wt% of PTFE dry powder and Li6PS5Cl electrolyte, stir the mixture thoroughly in a mortar and pestle, and transfer the mixture to a smooth stainless steel plate. Repeatedly roll-form the mixture with a stainless steel roller to form an electrolyte membrane with a thickness of 20 μm, which is the sulfide Li6PS5Cl solid electrolyte film.
[0020] Solid electrolyte composite membrane ion conductivity test: During the measurement, the solid composite electrolyte membrane is first cut into discs with a diameter of 18um, and then the solid composite electrolyte membrane is made into a stainless steel / solid electrolyte / stainless steel blocking battery. The two poles are connected to the test data line of the electrochemical workstation. At room temperature, the AC impedance spectrum is measured by the electrochemical workstation to determine the impedance value, with a frequency range of 0.1-1 MHz.
[0021] The ionic conductivity curve of the pre-fiberized sulfide solid electrolyte composite membrane is shown in Figure 1 , the ionic conductivity σ (S / cm) of the solid composite electrolyte membrane is calculated according to the formula: σ=d / (Re × S), where d is the thickness of the solid electrolyte sheet being tested (cm), Re is the impedance (Ω), and S is the effective area of the solid composite electrolyte membrane being tested (cm, calculated from the diameter d). After testing, the impedance Re in the AC impedance spectrum is 3.34 Ω. According to the formula σ=d / (Re ×S), the ionic conductivity σ is 3.06*10 -4 S / cm. It can be seen that the solid electrolyte composite membrane shows good ionic conductivity, which provides a new material development solution for the design of all-solid-state thin-film lithium batteries.
[0022] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a pre-fiberized sulfide solid electrolyte composite membrane, characterized in that: First, the polytetrafluoroethylene (PTFE) emulsion is demulsified and dried to prepare pre-fiberized PTFE dry powder, and then the sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte and fiberized PTFE are mixed to directly prepare the sulfide solid electrolyte composite membrane through a solvent-free dry process of roller pressing at room temperature, including the following steps: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a scraper of 300-600 μm, then place the glass plate in a vacuum oven, keep it at 120°C for 8 h to evaporate the solvent, put the glass plate in a glove box, scrape off the PTFE film under argon protection and crush it to obtain pre-fiberized PTFE dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Mix sulfide lithium phosphorus sulfur chlorine Li6PS5Cl electrolyte and pre-fiberized PTFE dry powder in a mixing ratio of 0.5~2.5 wt%, stir the mixture thoroughly in a mortar and transfer it to a smooth stainless steel plate, and repeatedly roll-form it with a stainless steel roller to form an electrolyte membrane with a thickness of 20~30μm, which is the sulfide Li6PS5Cl solid electrolyte film.
2. The method for preparing a pre-fiberized sulfide solid electrolyte composite membrane according to claim 1, characterized in that: Prepare as follows: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a 300 μm scraper, then place the glass plate in a vacuum oven and keep it at 120°C for 8 h to evaporate the solvent; finally, put the glass plate in a glove box, scrape off the PTFE membrane under argon protection and crush it to obtain PTFE membrane dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Weigh 0.2 g of pre-fiberized PTFE dry powder and 20 g of sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte, mix them in a mass ratio of 1 wt% of PTFE dry powder and Li6PS5Cl electrolyte, stir the mixture thoroughly in a mortar and pestle, and transfer the mixture to a smooth stainless steel plate. Repeatedly roll-form the mixture with a stainless steel roller to form an electrolyte membrane with a thickness of 20 μm, which is the pre-fiberized sulfide Li6PS5Cl solid electrolyte composite membrane.
3. The method for preparing a pre-fiberized sulfide solid electrolyte composite membrane according to claim 1, characterized in that: Prepare as follows: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a 400 μm scraper, then place the glass plate in a vacuum oven and keep it at 120°C for 8 h to evaporate the solvent; finally, put the glass plate in a glove box, scrape off the PTFE membrane under argon protection and crush it to obtain PTFE membrane dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Weigh 0.4 g of pre-fiberized PTFE dry powder and 20 g of sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte, mix them in a mass ratio of 2 wt% of PTFE dry powder and Li6PS5Cl electrolyte, stir the mixture thoroughly in a mortar and transfer it to a smooth stainless steel plate, and repeatedly roll-form it with a stainless steel roller to form an electrolyte membrane with a thickness of 30 μm, which is the sulfide Li6PS5Cl solid electrolyte film.
4. The method for preparing a pre-fiberized sulfide solid electrolyte composite membrane according to claim 1, characterized in that: Prepare as follows: a. Treatment of pre-fiberized PTFE dry powder: Weigh a PTFE emulsion with a solid content of 60 wt%, apply it on a glass plate with a 600 μm scraper, then place the glass plate in a vacuum oven and keep it at 120°C for 8 h to evaporate the solvent; finally, put the glass plate in a glove box, scrape off the PTFE membrane under argon protection and crush it to obtain PTFE membrane dry powder; b. Preparation of sulfide Li6PS5Cl solid electrolyte film: Weigh 0.5 g of pre-fiberized PTFE dry powder and 20 g of sulfide lithium phosphorus sulfur chloride (Li6PS5Cl) electrolyte, mix them in a mass ratio of 2.5 wt% of PTFE dry powder and Li6PS5Cl electrolyte, stir the mixture thoroughly in a mortar and transfer it to a smooth stainless steel plate, and repeatedly roll-form it with a stainless steel roller to form an electrolyte membrane with a thickness of 20 μm, which is the sulfide Li6PS5Cl solid electrolyte film.
5. A pre-fiberized sulfide solid electrolyte composite membrane, characterized in that Prepared according to any one of claims 1 to 4.
6. Use of the pre-fiberized sulfide solid electrolyte composite according to claim 5 in an all-solid-state lithium battery.
7. A method for applying the pre-fiberized sulfide solid electrolyte composite in an all-solid-state lithium battery according to claim 6, characterized in that: When applied to solid-state batteries, the pre-prepared pre-fiberized sulfide solid electrolyte composite membrane needs to be placed in a mold and surface pressed under a pressure of 300 MPa; when assembling the battery, carbon-coated LiCoO2 material is selected as the positive electrode and lithium-indium alloy as the negative electrode to prepare a solid-state battery.
Citation Information
Cited By
Dry-method membrane preparation method, dry-method electrode pole piece, preparation method of dry-method electrode pole piece and battery
CN120149337A
Dry film forming method, dry electrode sheet and preparation method thereof, and battery
CN120149337B